A review of the impact of maize-legume intercrops on the diversity and abundance of entomophagous and phytophagous insects - Pierre,Jacques Fils; Jacobsen,Krista L.; Latournerie-Moreno,Luis; Torres-Cab,Walther J.; Chan-Canché,Ricardo; Ruiz-Sánchez,Esau (PeerJ, 2023)
In many parts of the world, chemical pesticides are the primary method of pest control in maize (Zea mays L.) crops. Concerns about the negative consequences of chemical pesticide use on people’s health and the environment, as well as the emergence of insecticide resistance, have accelerated attempts to discover alternatives that are effective, low-risk, and cost-effective. Maize-legume intercropping systems are known to have multiple benefits to agroecosystem functioning, including pest regulation. This review focuses on the influence of maize-legume intercropping systems on insect diversity and abundance as a mechanism for insect pest regulation in maize crops. First, this review combines knowledge of maize-legume intercrops, with a particular emphasis on the mechanism by which this practice attracts beneficial insects (e.g., predators, parasitoids) to reduce pest damage in intercropping systems. In addition, the pairings of specific legume species with the greatest potential to attract more beneficial insects and therefore reduce maize pests are also discussed. Finally, future research needs are also recommended. Findings are reviewed in the context of looking for long-term management strategies that can increase the adoption of integrated pest management programs in maize-based production systems.
Keywords: Maize; Legume; Intercropping; Entomofauna; Parasitoids; Predators; Biological control